A continuous-time area detector servo demodulator for hard disk drives - Garrido, Nuno (2012)
This paper presents a continuous-time servo demodulator for magnetic disk drives implemented as a programmable current-mode operated Gm-C filter. This first order filter consists of pseudo-differential balanced transconductors and of a MOSFET bank array to implement a variable integrating capacitor. Simulation results are presented.